Case Report: Fatal massive hemoptysis secondary to pulmonary actinomycosis: a diagnostic and therapeutic challenge in a multidisciplinary approach - Yang, Qiong-Fang; Shu, Cai-Min (Frontiers in Medicine, 2025)
BackgroundActinomyces infections tend to involve the head and neck, while lung infections are relatively rare, and fatal hemoptysis due to pulmonary actinomycosis is even rarer.Case presentationA 74-year-old male patient who presented with a cough with intermittent hemoptysis for 17 months was admitted to the hospital for the fourth time on June 24, 2024. At the first visit (15 months ago), a computed tomography (CT) scan of the chest revealed a high-density shadow in the right middle bronchus (suggesting a foreign body to be drained) and an infected lesion in the lower lobe of the right lung. Hemoptysis was temporarily relieved after bronchoscopic removal of the foreign body and anti-infective treatment. Four months later, the patient was readmitted to the hospital due to a recurrence of hemoptysis. CT showed a lesion in the right lower lobe of the lung with cavitation, and bronchoscopy showed no abnormality. The pathology of percutaneous lung puncture biopsy suggested acute and chronic inflammation, and the patient was discharged under oral treatment with moxifloxacin. Four months later, the patient was admitted to the hospital for the third time because the hemoptysis volume had increased to 50 ml/day. Digital subtraction angiography-guided bronchial artery embolization was performed, and hemoptysis was controlled after the operation. Six months later, the patient was re-admitted to the hospital because of sudden hemoptysis as an emergency. Various medications were ineffective in stopping the hemoptysis, and the hemoptysis recurred; the volume was about 150 ml, with a sudden drop in blood oxygen saturation level to 82%. Due to the possibility of asphyxiation by blood clot, emergency bronchoscopic balloon occlusion was performed to stop bleeding, and right lower lobectomy was performed after multidisciplinary consultation. Post-operative pathology showed that the lung tissue was accompanied by tracheal dilatation, pus accumulation, and inflammatory granulomatous changes, with positive periodic acid Schiff staining, supporting actinomycetes infection. The patient continued anti-actinomycosis treatment for 1 month after surgery, and his condition stabilized after 8 months of follow-up.ConclusionsImaging of pulmonary actinomycosis is easily confused with tuberculosis and tumors and is difficult to diagnose. Pulmonary actinomycosis should be considered in patients with a lung mass shadow and recurrent hemoptysis. When life-threatening hemoptysis complicates pulmonary actinomycosis, surgical resection may effectively control the condition and improve the prognosis.